ПРИМЕНЕНИЕ НЕЧЕТКОЙ СИСТЕМЫ УПРАВЛЕНИЯ ДЛЯ МОНИТОРИНГА И УПРАВЛЕНИЯ ПАРАМЕТРАМИ ГАЗОПРОВОДА - Шомирзаев, Б.У. (FAN va JAMIYAT, 2024)
The article deals with the creation of a control system for a technological parameter of a gas pipeline - gas pressure using a fuzzy controller, the relevance of solving the problem of creating automatic control systems using the methods of intelligent technologies for automating the control and management of technological parameters. For fuzzification by the magnitude of the deviation of parameters in the pipeline, the authors proposed the use of a triangular form of membership functions of five terms and compiled a rule base consisting of 15 (fifteen) rules. According to the conclusion of the authors, the use of a control system based on fuzzy logic makes it possible to better adapt to the variable operation of the gas pipeline and does not require constant selection of the PID controller coefficients.